3D‐printed Microfluidic Device Based on Cotton Threads for Amperometric Estimation of Antioxidants in Wine Samples. Issue 1 (8th November 2017) - Carneiro, Emmanuelle A.; Agustini, Deonir; Figueiredo‐Filho, Luiz C. S.; Banks, Craig E.; Marcolino‐Junior, Luiz Humberto; Bergamini, Márcio F.
Abstract: The present work describes the evaluation of microfluidic electroanalytical devices constructed by a 3D printer using ABS (acrylonitrile butadiene styrene) polymer combined with cotton threads as microchannels. Screen‐printed carbon electrodes (SPCEs) were used as electrochemical detector for amperometric determination of gallic and caffeic acid in wine samples. Using optimal experimental conditions (flow rate of 0.71 μL s −1, applied potential of +0.30 V and volume of injection of 2.0 μL) the proposed method presented a linear response for a concentration range of 5.0×10 −6 to 1.0×10 −3  mol L −1 . The detection limits for gallic and caffeic acid were found to 1.5×10 −6  mol L −1 and 8.0×10 −7  mol L −1, respectively, with a sample throughput of 43 h −1 . The achieved results are in agreement with those found using the official Folin‐Ciocaulteu method. Abstract :